Long Memory versus Structural Changes in the Dynamics of Europe Brent-Oil Prices - Lamouchi, Rim; Alawi, Suha (The Arab Journal of Administration, 2021)
In this paper, we examine the potential of long memory and structural breaks properties in the Brent returns and the Brent volatility series. We analyze the series over the period 20/05/1987-22/01/2016, using long memory tests, we demonstrate strong evidence of long-range dependence in the daily return and volatility of oil prices. From structural breaks tests, we find two structural breaks that appear in 1991 and 2008 which coincides, respectively, with the Gulf war and the global financial crisis. We use the Perron and Qu (2010) test in order to discriminate the long memory from the spurious long memory in presence of structural break, the results show strong evidence in favor of long memory. Long memory plays a crucial role in describing the oil price dynamics and we can also confirm that despite the persistence of shocks, the evolution of series is predetermined by a long memory process.